Assessing the nurse’s knowledge regarding occupational hazards, its pre-disposing and preventive factors. - Joseph, Sonia; Nasir, Alia; Hussain, Amber (International Journal of Endorsing Health Science Research, 2021)
Background: Nurses are an essential part of the healthcare team and require sound knowledge, safety, and protection from occupational health hazards they encounter at work. Therefore, this study aimed to assess the nurse's knowledge regarding occupational hazards, their pre-disposing, and preventive factors. Methodology: A descriptive cross-sectional study was conducted among nurses working in surgical, general, ENT, ICU, and gyne ward of the Ziauddin and Civil hospital located in Karachi, Pakistan. A total of 157 registered nurses with a minimum of 6 months of work experience with a valid PNC license were included in the study. Systematic random sampling was used to select participants for the research. The knowledge regarding occupational hazards, pre-disposing factors, and preventive measures were recorded using a structured questionnaire. Results: Among 157 participants, the highest occurring occupational hazard was neck and back pain, 52.9%. The assessment of pre-disposing factors to occupational hazards revealed that 70.1% of nurses distinguished lack of adequate protective aids and equipment as one of the most common reasons for the occupational hazards. However, it is revealed by 77.7% of participants that proper training and retraining on safety measures, provision of protective aids and equipment could be possible ways of preventing occupational hazards. Conclusion: It is concluded that occupational health hazards are prevalent among nursing professionals, which can be reduced through owing responsibility, gaining appropriate knowledge and skills, warrant precautionary actions for avoidance to ensure their own and others' health and well-being.